The Lollipop with Lemon Aroma May Be Promising in Nausea and Vomiting in Pregnancy - Ismail Biyik; Fatih Keskin (Medical Network, 2020)
OBJECTIVE: To determine the effect of lemon-flavored lollipop on nausea and vomiting of pregnancy. STUDY DESIGN: This prospective case-control study included 67 first trimester pregnant women. The 12-hour Pregnancy-Unique Quantification of Emesis and Nausea score was calculated at the time of presentation to the hospital. The study group (32 cases) was given lemon-flavored lollipops while the control group (35 cases) did not receive lollipops. The Pregnancy-Unique Quantification of Emesis and Nausea scores of the patients were recalculated on the morning of the post-treatment day. RESULTS: The Pregnancy-Unique Quantification of Emesis and Nausea scores of the study group were higher (p=0.013) than in the control group on the day of admission. Pregnancy-Unique Quantification of Emesis and Nausea scores were similar between the groups on the day after hospital admission (p > 0.005). The Pregnancy-Unique Quantification of Emesis and Nausea difference values obtained by extracting the Pregnancy-Unique Quantification of Emesis and Nausea score on the day after hospital admission from the presentation Pregnancy-Unique Quantification of Emesis and Nausea score were higher in the study group (p=0.0046). Lemon-flavored lollipops were found to decrease nausea and vomiting of pregnancy. CONCLUSION: Lemon-flavored lollipops can be given especially to pregnant women who are concerned about the possible teratogenic effects of drug use in pregnancy. Lemon-flavored lollipops are cheap and easily accessible and therefore promising as a non-pharmacological complementary treatment for nausea and vomiting of pregnancy.